Cover Feature: Ligand‐Tuneable, Red‐Emitting Iridium(III) Complexes for Efficient Triplet–Triplet Annihilation Upconversion Performance (Chem. Eur. J. 34/2018). Issue 34 (5th June 2018) - Phillips, Kaitlin A.; Stonelake, Thomas M.; Chen, Kepeng; Hou, Yuqi; Zhao, Jianzhang; Coles, Simon J.; Horton, Peter N.; Keane, Shannon J.; Stokes, Emily C.; Fallis, Ian A.; Hallett, Andrew J.; O'Kell, Sean P.; et al.
Abstract : Photoluminescence from organometallic iridium(III) complexes can be tuned within the red part of the visible spectrum using ligand design. These compounds demonstrate remarkable application as efficient sensitizers in the upconversion of low energy light. More information can be found in the Full Paper by J. M. Beames, S. J. A. Pope, et al. onpage 8577 .